Harmoni Ilmu: Menyelami Dimensi Baru Pendidikan Islam melalui Integrasi Ilmu Pengetahuan, Teknologi, dan Seni - Ayu Lestari; Muhammad Guntur Alting (Jurnal Dirosah Islamiyah, 2024)
This research aims to explore the impact of integrating Science, Technology, and Arts in Islamic Education on the quality of learning and student development. A qualitative descriptive research method was employed with a case study approach in several secondary schools in a specific region. The research findings indicate that the application of audiovisual learning media, multimedia technology, and a scientific approach in teaching Islamic Religious Education contributes positively to students' motivation and academic achievement. Furthermore, the artistic approach in learning demonstrates that art can be used as a medium for a more profound and comprehensive understanding of religious concepts. This study also highlights the importance of balancing technological advancements with Islamic values in developing the Islamic Education curriculum. The development of a curriculum that considers the integration of Science, Technology, and Arts is expected to enhance the absorption of course materials and student creativity. Moreover, this research provides insights into the role of teachers in utilizing various learning resources that incorporate these elements, positively impacting the learning process.